Upaya Peningkatan Higher Order Thinking Skills (HOTS) Siswa Melalui Penerapan Model Inquiri di SMA Negeri 9 Tanjung Jabung Timur - Mohamad Muspawi; Suratno Suratno; Ridwan Ridwan (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
This study aims to determine the improvement of Higher Order Thinking Skills (HOTS) in Economics lessons through the Inquiry model in class X students. IPS.1 Tanjung Jabung Timur 9 High School. This research was conducted in Tanjung Jabung Timur 9 High School in the academic year 2018/2019. This research is classroom action research with research procedures covering the stages of planning, implementation, observation, and reflection. The subjects of this study were all students of class X. IPS.1 Tanjung Nabung Timur High School 9 9 which consisted of 36 students consisting of 16 male students and 20 female students. The object of this research is the application of the Inquiry model to improve Higher Order Thinking Skills (HOTS). Data collection techniques used were observation, interview, documentation, journal and test assessment. Analysis of data obtained by calculating the percentage of graduation of students in high-level thinking skills. The results of the study showed that there was an increase in Higher Order Thinking Skills in Economics in class X students. IPS.1 SMA N 9 Tanjung Jabung Timur. It can be seen that the average increase and graduation from cycle to cycle. In the first cycle the percentage of student graduation was 36.11% and HOTS was 13, and in the second cycle it increased by 41.67% with HOTS as many as 15.